Obe-related stress among township school teachers - Motseke, Masilonyana Jacob (Welkom: Central University of Technology, Free State, 2000)
The aim of this study is to investigate the contribution of OBE to the stress experienced by township school teachers. Based on literature study, a questionnaire, the Outcomes-Based Education Teacher Stress Questionnaire (OBETSQ) was developed. The questionnaire was administered to 185 teachers in the Free State Goldfields and surrounding areas. Interviews were also conducted. Data collected was analysed qualitatively and quantitatively. The empirical research revealed that conditions in the township schools, including teacher training, were not conducive for the introduction of OBE. The introduction of OBE in these schools, therefore, contributed enormously to the stress situation of township teachers. Lastly, several recommendations were made, including the retraining of teachers and provision of resources and facilities.
Thesis
Keywords: Competency-based education - South Africa; Teachers - Job stress; Outcomes-based education (OBE); outcomes; stress; teacher stress; stressors; theories; townships; township schools; teacher training and learners